Formation of Protoclusters in the Tank Industry of the Urals in 1941-1945 - Zapariy, Vladimir Vasilyevich; Zapariy, Vasily Vladimirovich; Guanshan, Zhang (Economy of Regions, 2017)
The article considers the process of the formation of the tank industry in the Urals during the Great Patriotic War in connection with the aspects of regional development within the large territorial and industrial entities. In modern economic science, such territorial industrial associations are known as «clusters». They mean a group of enterprises, united by a common technological process and management, concentrated to achieve a specific production and economic goal. In the modern world, such associations play a decisive role in managing high-tech and innovative industries in the realities of the market economy. This applies both to the civilian and military engineering, including the large and small production, both to public and private ones. In the Sverdlovsk region, at the present time, there is a large tank-building cluster, concentrated around the Uralvagonzavod Corporation (UVZ) in Nizhny Tagil, which includes a number of production units in the territory of the Ural Federal District. The tank production, which originated in the Urals in 1940-s, and fast developed during the Great Patriotic War, shows the typical features of modern cluster structures. This suggests the existence of so-called «protocluster» formations within the tank industry of the Ural economic region in 1941-1945. The article presents the features of the formation of two major protoclusters in the Sverdlovsk and Chelyabinsk regions, which have concentrated in their borders a significant economic potential for the production of medium and heavy tanks, as well as automatic control systems based on them. The article discusses the chronology of their occurrence, the member enterprises, the features of their cooperation and interaction within the unified system of the Peoples Commissariat of Tank Industry of the Union of Soviet Socialist Republics (USSR NKTP).